An Analysis Of Adjectives In Joyce Carol Oates “Where Are You Going Where Have You Been” - Lia Khalisa (Journal of Innovative and Creativity, 2025)
The purpose of this study is to analyze the adjectives in Joyce Carol Oates’ short story ’Where Are You Going Where Have You Been’. The analysis was focused on What kind of adjectives that are widely used found in Joyce Carol Oates’ Where Are You Going Where Have You Been adjectives and the positions of adjectives. This research study was conducted by using descriptive qualitative design. The results of the study showed that there were four kinds of adjectives found in Joyce Carol Oates’ Where Are You Going Where Have You Been. They were descriptive adjectives, predicative adjectives, attributive adjectives and limiting adjectives. The positions of adjectives found in Joyce Carol Oates’ Where Are You Going Where Have You Been were before a noun and after a verb.